Promoting the Consumption of Fish-Based Processed Products as A Strategy to Improve Children's Nutrition in Majakerta Village, Majalaya District, Bandung Regency - Aisyah, Aisyah; Maulina, Ine; Mulyani, Yuniar (International Journal of Research in Community Services, 2025)
Efforts to increase fish consumption offer numerous benefits, not only enhancing intelligence but also boosting the fisheries industry. Currently, stunting remains a concerning issue, and data indicates that fish consumption is not evenly distributed across Indonesia. This represents one of the health problems that serves as an indicator of the health and well-being of a community. One of the themes of this community service program (or also known as PPM in Indonesia) is raising awareness about improving children's nutrition among the residents of Majakerta Village, Majalaya District, Bandung Regency. The implementation of the program is conducted in collaboration with student community service (or also known as KKN in Indonesia) activities. The primary objective of this program is to improve children's nutrition through the promotion of fish-based processed food consumption and to educate mothers in Majalaya District about recognizing stunting symptoms and addressing them. The main target of this program is children aged 612 years. The method used in this awareness campaign includes educational games about fish and fish-based processed food to make the material easier for elementary school children to understand. Additionally, one type of fish-based processed food is distributed for children to taste directly, aiming to increase their interest in fish consumption. The results achieved include improved knowledge about the importance of eating fish due to its many health benefits.